Development and application of an efficient, accurate, and environmentally friendly liquid chromatography–tandem mass spectrometry method for the determination of five Alternaria toxins in wheat - Huiyuan Lang; Zengwang Guo; Yu Wu; Li Li; Hongmei Liu; Lianzhou Jiang; Songxue Wang; Jin Ye (Food Chemistry: X)
The contamination of Alternaria toxins poses a potential risk to human health. This study developed a rapid, efficient, and environmentally friendly method for the simultaneous determination of five types of Alternaria toxins in wheat using high-precision and stable isotope liquid chromatography tandem mass spectrometry. The comparison between dilution method and solid-phase extraction method shows that the former achieves satisfactory results with a simple and convenient sample purification method. The quantitative limit range is 0.88 to 1.68 μg/kg. The recoveries are between 81.40% and 102.68%, with RSD less than 11.95%. The method was used to analyze 60 samples from the main wheat producing areas in China. The results showed that Tenuzonic acid had the highest detection rate (100%), followed by Tentoxin (95%), Alternariol (66.67%), and Alternariol monomethyl ether (53.33%). There is a certain pollution risk that needs to be taken seriously and monitoring should be strengthened.